Spiritualitas Dalam Akuntansi Sang Pembebas Dari Kuasa Kapitalisme - Ida Ayu Nursanty; Endang Kartini; I Made Murjana (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
The objectives of the research are to criticize the modern accounting is entrenched under the auspices of capitalism, especially accounting in Indonesia, and to an alternative idea for a better one. Is done as there as a strength that accounting for capitalism has reached a deadlock in answering current problems. Conventional accounting as a product of the modern era which has the spirit of capitalism is always oriented towards maximizing profit and rationality of recording. The impact of this understanding makes accounting a means of legitimating certain parties to seek maximum profit, without paying attention to other artificial interests. Through a rasionalis spiritualist approach, the research suggests the internalization of